Ethnic minorities in Borneo: the Kimaragang people - Victor B. Pangayan; A.S. Hardy Shafii (Penerbit UMS, 2021)
This article presents an overview of the Kimaragang ethnic group, where the Kimaragang ethnic group is one of the indigenous sub-ethnic groups of Sabah, with typical settlements in Kota Marudu and Pitas. This article discusses the origins of the Kimaragang ethnic group, their earliest habitation, their language, economy, and sociocultural. It is anticipated that the material in this article will assist researchers, educators, institutions, and organisations in continuing to impart the culture of the indigenous peoples of Sabah, both directly and indirectly, through diverse research, publications, and documentation.